PENGARUH PROGRAM LITERASI, PERAN GURU DAN FASILITAS PERPUSTAKAAN TERHADAP MINAT BACA SISWA DENGAN KEINGINTAHUAN SISWA SEBAGAI VARIABEL MEDIASI - Nurhandasah, Afita; Pramusinto, Hengki; Rahmaningtyas, Wisudani (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The purpose of this study is to determine determine whether there is a positive and significant influence of goal achievement orientation, family environment and school facilities on student achievement motivation students of X Grade at SMKN 1 Kudus simultaneously or partially. The population of this study X Grade at SMKN 1 Kudus and this study is a population study with 137 respondents. The research design of this study is quantitative approach and the data collection using questioner. The method of data analysis is descriptive analysis, linear regression and hypothesis test. Results obtained from multiple regression analyzes in this study were Y = 4.935 + 0.332 (X1) + 0.306 (X2) + 0.311 (X3) + e. There was influence simultaneously equal to 51.9%, while partially goal achievement orientation have positive and significant effect equal to 10.6%, family environment have positive and significant influence equal to 14.5%, and school facilities have positive and significant influence equal to 8.5%. The conclusion of this research is the influence of goal achievement orientation, family environment and school facilities on student achievement motivation students X at SMKN 1 Kudus simultaneously and partially